Interpolating refinable functions and wavelets for general scaling - Dahlke, Stephan; Maass, Peter (Numerical functional analysis and optimization, 1997)
This paper introduces a general procedure for constructing interpolating refinable functions for arbitrary dilation matrices. The key ideas are based on the construction presented in [24]. Several families of interpolating refinable functions are computed exlicitly. They originate from convolution products of some simple functions, either generalized Haar functions or Laplace schemes. A suitable correction is added to obtain interpolating solutions. AMS Subject classification: Primary 26B05, 41A05, 41A15, Secondary 41A30, 41A63